Parasite infection alters host stable‐isotope composition under controlled feeding. (November 2016) - Pulkkinen, Katja; Aalto, Sanni L.; Nykänen, Hannu
Summary: Stable isotopes are widely used for studying trophic relationships, but variation driven by environmental conditions or food availability complicates the interpretation of trophic dynamics. Parasites are ubiquitous and known to affect physiological functions of their hosts, but only few studies have assessed the effects of parasites on isotope composition of hosts. We measured the changes in two of the most commonly used stable isotopes in food‐web studies, nitrogen (i.e. 15 N: 14 N ratio; denoted as δ 15 N) and carbon ( 13 C: 12 C; δ 13 C) in Daphnia hosts exposed to infection by a parasitic micosporidian in the laboratory. Isotopic signatures of hosts fed a standardised controlled diet were compared with uninfected animals under conditions of high food availability and under food limitation. Parasite infection led to enriched δ 15 N and δ 13 C values that were associated with decreased growth and decreased lipid content, indicating energy limitation comparable to that in food‐limited animals. However, enrichment in 13 C values was apparent sooner in infected well‐fed animals than in the food‐limited animals, suggesting strong parasite‐induced effects on host C‐metabolism. By using experimental exposure to parasite infection and a standardised diet, our study excluded the effects of changes in food sources via parasite‐induced altered habitat or feeding behaviour on host isotope composition and demonstrated for the first time that parasite infection directly alters the isotopic values of the host. Our study demonstrates that parasite‐induced changes in isotope values may add to the variability in the estimates of the contribution of each food type assimilated by consumers, and thus should be taken into account during investigations of trophic relationships and food webs.